1993
DOI: 10.2165/00019053-199304060-00007
|View full text |Cite
|
Sign up to set email alerts
|

Annual Costs of Benign Prostatic Hyperplasia in New Zealand

Abstract: Benign prostatic hyperplasia (BPH) has been regarded as part of the normal aging process in men and little attention has been focused on the cost of the disease in New Zealand. The purpose of this study was to estimate the direct and indirect costs of treating BPH in both the public and the private sectors in New Zealand. The costs of treatment were estimated from public and private hospital data on admissions for BPH, obtained from the New Zealand Department of Health, medical insurance reimbursement schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…One study reported that total medical expenditures with BPH were US$776 million in the United States in the year of 2000 2. Another study reported that the annual cost of treating BPH in New Zealand was about US$8.73 million 3. In addition, Saigal and Joyce4 indicated that the annual spending for BPH was US$5729 per person-year for patients aged 45–64 years.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that total medical expenditures with BPH were US$776 million in the United States in the year of 2000 2. Another study reported that the annual cost of treating BPH in New Zealand was about US$8.73 million 3. In addition, Saigal and Joyce4 indicated that the annual spending for BPH was US$5729 per person-year for patients aged 45–64 years.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no empiric studies assessing the economic impact of BPH in the U.S. or in a specific population such as VA. Totally there have been three cost of illness studies in literature, one in UK, one in Sweden and one in New Zealand (Scott & Scott, 1993;Drummond, Mcguire, Black, Petticrew & McPherson, 1993;Ahlstrand, Carlsson & Jonsson, 1995). However, only one of these studies estimated the cost of diagnosis for BPH (in New Zealand).…”
Section: Discussion For Objective Seven Resultsmentioning
confidence: 99%
“…ll Guy Scou (2001) If Iloprost is adnrinistered for 20 days at a pharmaceutical cost o [$ I 85 per day in a hospital setting at a rvard cost of $330 per day (Scott and Scott, 1993) the total medical cost per patient would be $ 10,300 compared with a cost of $ 19,020 (procedure method) per critical leg ischaenria patient undergoing an amputation. Medical cost savings per amputation avoided were $8,720.…”
Section: I42 Methodsmentioning
confidence: 99%